2014
DOI: 10.1007/s11682-014-9324-x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of EEG functional connectivity and EEG power spectra in overweight and obese patients with food addiction: An eLORETA study

Abstract: We evaluated the modifications of electroencephalographic (EEG) power spectra and EEG connectivity in overweight and obese patients with elevated food addiction (FA) symptoms. Fourteen overweight and obese patients (3 men and 11 women) with three or more FA symptoms and fourteen overweight and obese patients (3 men and 11 women) with two or less FA symptoms were included in the study. EEG was recorded during three different conditions: 1) five minutes resting state (RS), 2) five minutes resting state after a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 92 publications
4
42
1
Order By: Relevance
“…The increasing number of published studies that investigate FA do so in conjunction with other formally recognised mental health conditions, such as depression and related symptoms (20) . Indeed, epidemiological research indicates that a clustering of comorbidities is present in people reporting depression, such that the presence of depression, particularly in young adult males, is associated with twice the risk of obesity, smoking, spending more time in sedentary activities, and behaviours associated with drug and alcohol use relative to nondepressed young adults (26) .…”
Section: Introductionmentioning
confidence: 99%
“…The increasing number of published studies that investigate FA do so in conjunction with other formally recognised mental health conditions, such as depression and related symptoms (20) . Indeed, epidemiological research indicates that a clustering of comorbidities is present in people reporting depression, such that the presence of depression, particularly in young adult males, is associated with twice the risk of obesity, smoking, spending more time in sedentary activities, and behaviours associated with drug and alcohol use relative to nondepressed young adults (26) .…”
Section: Introductionmentioning
confidence: 99%
“…Using exact low-resolution brain electromagnetic tomography (eLORETA) software allows to considerably removing this confounding factor (Pascual-Marqui, 2007). For this reason, in the recent years this software has been used to evaluate non-invasive functional connectivity measures, as respect with various EEG bands in different task and different fields of investigations both in psychological and neuroscientific studies such as the ones concerning: major depression (Olbrich et al, 2014), cognitive decline (Vecchio et al, 2014), food-addiction (Imperatori et al, 2015) and mindfulness meditation (Lehmann et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][6][7][8][9] Moreover, it has been observed that addictive eating symptoms may be associated with neural activation of brain regions involved in drug addiction (i.e., hippocampus, amygdala, insula, caudate) in response to anticipated intake of palatable food and to the retrieval of the sensory properties of favorite foods. [10][11][12] Gearhardt and colleagues 13 proposed operational criteria for a Food Addiction (FA) diagnosis according to the Diagnostic and Statistical Manual of Mental Disorders criteria for substance dependence. 14 These criteria were used to devise the Yale Food Addiction Scale (YFAS), an instrument assessing diagnosis and severity of FA.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this procedure has previously been used to investigate the neurophysiological correlates of FA 12 6 with low FA symptoms) have a different pattern of activation of brain regions in response to the intake of palatable foods.…”
Section: Introductionmentioning
confidence: 99%